1997
DOI: 10.1091/mbc.8.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Topogenesis of a nucleolar protein: determination of molecular segments directing nucleolar association.

Abstract: To identify the element(s) in nucleolar proteins which determine nucleolus-specific topogenesis, we have used different kinds of cDNA constructs encoding various chimeric combinations of mutants of the constitutive nucleolar protein N038 (B23): 1) with an amino terminally placed short "myc tag"; 2) with two different carboxyl terminally attached large a-helical coiled coil structures, the lamin A rod domain or the rod domain of vimentin; 3) with the sequence-related nucleoplasmic histone-binding protein nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 77 publications
3
46
0
Order By: Relevance
“…However, glutathione S-transferase-pull-down experiments, yeast two-hybrid analysis, and native gel electrophoresis demonstrate that DEK can physically associate with itself and exists in several multimeric forms (data not shown). Dimerization would allow mutant forms of DEK to associate with endogenous DEK and "piggyback" to IGCs following TSA treatment (65). This phenomenon therefore masks the identification of the lysine responsible for sub-nuclear movement of DEK using site-directed mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, glutathione S-transferase-pull-down experiments, yeast two-hybrid analysis, and native gel electrophoresis demonstrate that DEK can physically associate with itself and exists in several multimeric forms (data not shown). Dimerization would allow mutant forms of DEK to associate with endogenous DEK and "piggyback" to IGCs following TSA treatment (65). This phenomenon therefore masks the identification of the lysine responsible for sub-nuclear movement of DEK using site-directed mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Although protein B23 is known to oligomerize (20,32,33), this is the first study to correlate its oligomerization with molecular chaperone activity. Clearly, no chaperone activity was retained in mutant proteins that were monomeric; however, it cannot be ruled out that these mutants simply lacked a substrate-binding site because this seems to reside in the N-terminal third of the molecule.…”
Section: Figmentioning
confidence: 97%
“…The tion and probably exists as a hexamer or larger oligomer in the cell (20,32,33). Gel filtration chromatography was used to assess the oligomeric states of the mutant proteins to determine the possible relationship of this property with chaperone activity.…”
Section: The Ribonuclease Activity Requires Segments From the Centralmentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions where significant amounts of the monomer were present, NPM was capable of DNA binding, whereas conditions that strongly favored oligomerization caused a nearly complete abolition of this DNA binding activity [32]. Recently, it was reported that the NPM isoforms, NPM1 and NPM1.2, can form oligomers in vivo and in vitro [28,35,36], but the RNA binding activity of NPM1 is impaired by hetero-oligomerization with NPM1.2 [28]. Another study has shown that the reversible change of oligomerization between the hexameric and monomeric forms of NPM is found to occur most frequently in cells in G1 and G1/S phases [37].…”
Section: Npm Structurementioning
confidence: 99%